Network meta-analyses in child and adolescent psychiatry: a meta-review - Cortese, S; Tomlinson, A; Cipriani, A (Elsevier, 2018)
Objectives Network meta-analyses (NMAs) are gaining traction as the preferred method for evidence synthesis of intervention studies. This review aimed to summarize the basics of NMAs and conduct a meta-review of available NMAs on the treatment of child and adolescent psychiatric disorders by appraising their quality. Method PubMed (Medline), PsycInfo, Embase, Ovid Medline, and Web of Knowledge were systematically searched (last update January 9, 2018). The quality of each included NMA was appraised using the AMSTAR-2 tool and the PRISMA-NMA checklist, which include specific items for NMAs. Results Eighteen NMAs (6 on attention-deficit/hyperactivity disorder; 4 on psychotic disorders; 2 on depression; 2 on anxiety disorders; 1 on obsessive compulsive disorder; 1 on disruptive behavior disorder, 1 on bipolar disorder, and 1 on antipsychotics across disorders) were retrieved. Results from the AMSTAR-2 assessment showed that only 27% of appraised NMAs were rated as moderate quality; most were rated as low (33%) or critically low (40%) quality. Only 3 of the appraised NMAs reported on all PRISMA-NMA items specific for NMAs; the network structure was graphically presented in most NMAs (80%), and inconsistency was described in only 47%. Conclusion Given the paucity of head-to-head trials in child and adolescent psychiatry, NMAs have the potential to contribute to the field, because they provide evidence-based hierarchies for treatment decision making, even in the absence of trials directly comparing at least 2 treatments. However, because of important limitations in the included NMAs, additional methodologically sound NMAs are needed to inform future guidelines and clinical practice in child and adolescent psychiatry.